1996
DOI: 10.1161/01.cir.94.12.3246
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Adult Hypertension, Diabetes Mellitus, and Obesity in US Men

Abstract: These findings support the hypothesis that early life exposures, for which birth weight is a marker, are associated with several chronic diseases in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
516
6
20

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 830 publications
(569 citation statements)
references
References 18 publications
27
516
6
20
Order By: Relevance
“…12 This programming may have beneficial effects on short term but predispose the individual to diseases in adulthood, including obesity and insulin resistance. 11 Our findings are in line with previous studies showing associations of both low and high birth weight with an increased risk of developing overweight. [49][50][51] Recent studies have reported that this might be dependent on programming of lean body mass as well as programming of fat mass.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…12 This programming may have beneficial effects on short term but predispose the individual to diseases in adulthood, including obesity and insulin resistance. 11 Our findings are in line with previous studies showing associations of both low and high birth weight with an increased risk of developing overweight. [49][50][51] Recent studies have reported that this might be dependent on programming of lean body mass as well as programming of fat mass.…”
Section: Discussionsupporting
confidence: 93%
“…These adaptations predispose the individual to increased fat mass and insulin resistance postnatally. 11,12 However, studies relating these early life factors with more detailed measures of fat mass are scarce. 13 We examined the development of subcutaneous fat mass, measured by SFT, in the first 2 years of life in a population-based, prospective cohort study from early fetal life onward.…”
Section: Introductionmentioning
confidence: 99%
“…People who were small at birth have an increased risk of type 2 diabetes in later life [1][2][3][4][5][6][7]. One interpretation of this association is that an adverse intrauterine environment permanently impairs glucose homeostasis, primarily by inducing insulin resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…14 Finally, increased metabolic risk is seen not only with low birth weight, but also with high birth weight. 15 Thus, although there is strong evidence that foetal nutrition impacts on metabolic homeostasis in later life, the effects of maternal/foetal and neonatal nutrition appear highly complex and far from unravelled.…”
Section: Experimental Data Regarding Foetal/neonatal Nutrition and Mementioning
confidence: 99%